The application of PIXE and PIGE for the studying of impurities distribution in space near the seam at welding products out of the Zr1%Nb alloy - Levenets, V.V.; Shchur, A.O.; Petelguzov, I.A.; Belash, N.N. (Вопросы атомной науки и техники, 2009)
In this work the nuclear-physics methods of analysis of the content of a matter based on the using of proton induced characteristic X-ray emission of the atoms and momentum γ-ray emission from nuclear reaction was applied to determine the gaseous impurities N, O, F and elements B, Ca, Ti, V, Cr, Fe, Ni, Cu, Nb, Mo, Cd, Sn, Hf, Pb, in zirconium alloys and to research the absorption of oxygen, nitrogen and fluorine by a matter of tubes made from alloy Zr1%Nb during the procedures of the fabricating of models of fuel assembly. There are a number of the factors, which affect negatively on material of shells and fuel assembly as hole at a technological process of manufacture fuel assembly for nuclear reactor VVER-1000. Such factors are the interstitial impurities (oxygen, nitrogen), hitting in metal during operations of hyper thermal processing, in particular, at welding details of fuel assembly. The gaseous impurities of atmosphere of the weld – nitrogen and oxygen inserted in a welding seam can degrade rust resistance of a seam and slash a plasticity of a material. A surface of manufactured fuel assembly or samples for researches can to be polluted by fluorine from pickling compositions at the stage of a chemical polish by an etching in fluorine inclusive solutions. Fluorine, as is known, is a fissile element lowering rust resistance and of details of ends of fuel assembly.